Analisa Perancangan Pengendali Wireless Menggunakan Microcontroller AT 89S2051 - Sugiarto, Agus (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2016)
Wireless is the control system and data delivery with no cables. The advantages of the wireless system is the system can save expenses of cable channels that are still relatively expensive, it is very easy to install, most users can understand technical instructions of use Wireless in a short time, easy to implement and reduces cable clutter that crisscrossed, so it will give the impression neatly. Advances in science and technology have been encouraging people to try to overcome all the problems that arise in the vicinity. These human limitations gradually be solved with ditemukanya technologies - new technologies, one of which is a motion on the robot. Currently there are some robot controller technology that can facilitate human in performing daily activities namely technology controller using a cable, Line Follower and Wireless Systems.